Effect of indel variants within the sorting nexin 29 (SNX29) gene on growth traits of goats. Issue 5 (3rd October 2022) - Bi, Yi; Chen, Yuhan; Xin, Dongyun; Liu, Tingting; He, Libang; Kang, Yuxin; Pan, Chuanying; Shen, Weijun; Lan, Xianyong; Liu, Mei
Abstract: The sorting nexin 29 gene ( SNX29 ) is a well-known regulator of myocyte differentiation and proliferation. In this work, two indels (17-bp and 21-bp) were identified in the goat SNX29 gene, and their effects on the growth traits of 1, 759 Shaanbei white cashmere (SBWC) goats were analyzed. Both indels had three genotypes [homozygote wild type (II), heterozygote (ID), and homozygote mutation (DD)] and displayed medium genetic diversity (0.25 < polymorphism information content (PIC) < 0.50) in the population. The 17-bp indel was significantly associated with chest width ( p = 0.009), body weight ( p = 0.021), and chest depth ( p = 0.032), with the II genotype dominant. The 21-bp indel was significantly associated with chest width ( p = 0.001), chest depth ( p = 4.8E-5), heart girth ( p = 0.007), and hip width ( p = 0.002). Because the two indels were in the upstream (17-bp) and intron (21-bp) regions of the SNX29 gene, transcription factor binding sites were predicted. The IRF5 and MYC could bind with the 17-bp indel and 21-bp indel sequences, respectively. This study indicates that SNX29 is a promising candidate gene that can be used to improve meat production in goat breeding.